Mycotoxicoses of ruminants and horses - Riet-Correa, Franklin (2013)
In the current study, mycotoxicoses of ruminants and horses are reviewed, with an emphasis on the occurrence of these diseases in South America. The main mycotoxicoses observed in grazing cattle include intoxications by indole-diterpenoid mycotoxins (Paspalum spp. contaminated by Claviceps paspali, Lolium perenne infected by Neotyphodium lolii, Cynodon dactylon infected by Claviceps cynodontis, and Poa huecu), gangrenous ergotism and dysthermic syndrome (hyperthermia) caused by Festuca arundinacea (syn. Festuca elatior) infected by Neotyphodium coenophialum (syn. Acremonium coenophialum), and photosensitization in pastures contaminated by toxigenic Pithomyces chartarum. Other mycotoxicoses in grazing cattle include slaframine toxicity in clover pastures infected by Rhizoctonia leguminicola and diplodiosis in cattle grazing in corn stubbles. The mycotoxicoses caused by contaminated concentrated food or byproducts in cattle include poisoning by toxins of Aspergillus clavatus, which contaminate barley or sugar beetroot by-products, gangrenous ergotism or dysthermic syndrome caused by wheat bran or wheat screenings contaminated with Claviceps purpurea, and acute respiratory distress caused by damaged sweet potatoes (Ipomoea batatas). The main mycotoxicosis of horses is leukoencephalomalacia caused by the fumonisins B1 and B2 produced by Fusarium spp. Poisoning by C. purpurea and F. elatior infected by N. coenophialum has also been reported as a cause of agalactia and neonatal mortality in mares. Slaframine toxicosis caused by the ingestion of alfalfa hay contaminated by R. leguminicola has also been reported in horses.